Insect infestations have an impact on the quality of climate reconstructions using Larix ring-width chronologies from the Tibetan plateau - Aryal, Sugam; Grießinger, Jussi; Arsalani, Mohsen; Meier, Wolfgang; Fu, Pei Li; Fan, Ze Xin; Bräuning, Achim (Ecological Indicators, 2023)
Insect outbreaks are proven to harm trees, reducing their biomass accumulation due to the defoliation of leaves during the growing season. Various defoliators are responsible for the formation of extremely narrow tree rings in different tree species. In climate reconstructions based on tree-ring width, such narrow rings are often considered as noise, because their formation is not entirely caused by climatic conditions. Thus, the impact of defoliators should be removed (nullified) for unbiased climate reconstructions. This study mainly describes a statistical approach to disentangle the effects of Larch budmoth(LBM) (Zeiraphera diniana) and climate for an unbiased temperature reconstruction in the Bai-Ma mountain area in Southwest China using Larix potaninii. After applying our new approach, growth-climate relationships improved significantly (p < 0.05), especially with minimum temperature during the growing season (June-September). The resulting temperature reconstruction (BTmin) covers the period 1712–2020 CE (313 years). Our final temperature reconstruction for the Bai-Ma area showed a wiggly trend from 1712 to 1980, with some cool periods (1791–1853 and 1888–1930) and warm episodes (1724–1745, 1854–1887, 1950–1967). During the recent 50 years, BTmin reveal an alarming warming trend of up to 0.4 °C per decade. We also observed a strong coherency of BTmin with regional temperature series. Furthermore, we detected a differential effect of various climate modes, with the most substantial impact of the Atlantic Multidecadal Oscillation (AMO) on BTmin (p < 0.01). Interestingly, the Pacific Decadal Oscillation (PDO) showed a coupled effect along with AMO on BTmin. As revealed in this study, removing the LBM effect improved the chronology's climate sensitivity, leading to a more robust transfer function and in terms of insect infestations unbiased climate reconstructions. Thus, it is recommended to check ring-width data for any periodicity potentially related to insect outbreaks and correct the original data before using tree-ring chronologies for climate reconstruction.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Defoliator; Dendrochronology; Larch budmoth; Minimum temperature; Outbreak; Yunnan

Multi-centennial reconstruction of drought events in South-Western Iran using tree rings of Mediterranean cypress (Cupressus sempervirens L.) - Arsalani, Mohsen; Grießinger, Jussi; Pourtahmasi, Kambiz; Bräuning, Achim (Palaeogeography, Palaeoclimatology, Palaeoecology, 2021)
Semi-arid regions are among the most vulnerable areas prone to the negative impacts of climate change. Long-term high-resolution proxy climate data will enable us to put the recent climate trends into a long-term context of natural climate variability. We developed the hitherto first regional ring-width chronology (1450–2015C.E.) from Cupressus sempervirens L. in the Zagros Mountains, western Iran and reconstructed precipitation variability for the semi-arid region during the period 1560–2015C.E. Climate-growth relationships revealed that precipitation and minimum temperatures are positively correlated with radial growth, whereas maximum temperatures reveal negative impacts. Spatial correlations with gridded precipitation data, Palmer drought severity index (PDSI), and standardized precipitation-evapotranspiration index (SPEI 01) further indicate that the climate signals contained in tree-ring width variations capture the precipitation variability in the Near East and other eastern Mediterranean regions. The southern Zagros Mts. experienced multiple megadroughts during the reconstructed period. The longest dry period occurred from 1956 to 1971 and the highest frequency of dry events occurred in the 20th century. In addition, documented famines in Iran occurred within prolonged droughts. The southern Zagros Mts. has experienced high frequency of extreme/severe dry events and long dry phases during the Little Ice Age (1560–1850C.E.). The reconstructed dry and wet events occurred irregularly, and one-year and two-year drought/wet events showed the highest frequency during the reconstructed period, highlighting the importance of sustainable water management strategies for the semi-arid southern Zagros region.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Climate change; Cupressus sempervirens; Dendroclimatology; Little Ice Age; Teleconnection patterns; Zagros Mountains

Tree-ring-based seasonal temperature reconstructions and ecological implications of recent warming on oak forest health in the Zagros Mountains, Iran - Arsalani, Mohsen; Grießinger, Jussi; Bräuning, Achim (International journal of biometeorology, 2022)
Abrupt changes in temperature have especially strong impacts on fragile ecosystems located in semi-arid regions. In this study, we analyzed tree-ring widths (TRW) of Mediterranean cypress (Cupressus sempervirens var. horizontalis) in the Zagros Mountains, Iran. Furthermore, we separately measured earlywood width (EWW) and latewood width (LWW) of Persian oak (Quercus brantii Lindl.) to examine if intra-annual resolution of tree-ring parameters of Q. brantii tree rings can be used as high-resolution paleoclimate proxies. Climate-growth relationships revealed that mean monthly maximum temperatures (Tmax) are a dominant factor determining radial tree growth and negatively affect both oak and cypress in the Zagros Mountains. Accordingly, we reconstructed two different seasonal windows of past Tmax variability, namely, January–March and June–August over the periods 1860–2015 and 1560–2015, respectively. Regime shift detection identified twelve warm and nine cold significant regime shifts in our summer Tmax reconstructions. The longest hot summer period occurred in the twentieth century, and two warm regime shifts occurred in 1999 and 2008. The highest values of the warm summer regime shift index occurred in 2008, which coincided with fungal pathogen attacks and insect outbreak of the oak leaf roller moth (Tortrix viridana L.) in the Zagros oak woodlands. Interestingly, we found common warm and cold periods in historic climate variability between the summer and winter Tmax reconstructions. Warm and cold regime shifts occurred simultaneously from 1955 to 2015, and significant regional warm summer and winter regime shifts have occurred between 2008 and 2015. The winter and summer Tmax reconstructions show high spatial correlations with large areas in West Asia, North Africa, and the eastern Mediterranean region. Our results strengthen initial studies on past climate variability in Iran and contribute to an enhanced understanding of past temperature variability in West Asia.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Earlywood width; Insect outbreak; Mediterranean cypress; Temperature reconstruction; Tree-ring width; Zagros oak woodland